Comorbidity of Menetrier’s disease and diabetes mellitus. A clinical case - P.M. Lyashuk; R.P. Lyashuk; Yu.F. Marchuk (Mìžnarodnij Endokrinologìčnij Žurnal, 2024)
We present a case report describing the diagnosis and management of a patient who presents with a rare diagnosis of Menetrier’s disease. This condition poses a diagnostic challenge to clinicians due to its nonspecific clinical presentation and is oftentimes misdiagnosed for more common gastric disorders. Menetrier’s disease is characterized by gastric mucosal hypertrophy and subsequent protein loss, resulting in gastric symptoms and widespread edema. While the etiology remains unclear, notable associations have been observed with Helicobacter pylori infection and overexpression of transforming growth factor alpha. The management often involves supportive measures with medical and surgical interventions for refractory cases and when necessary. This report includes a comprehensive review of the literature on the clinical presentation, diagnostic approach, and management of this rare disease. By documenting such cases in the medical literature, we aim to enhance the clinician’s ability to recognize and manage this disorder, thereby preventing the development of more severe manifestations such as diabetes mellitus. Menetrier’s disease is a rare disorder that should be suspected in patients with upper gastrointestinal complaints and hypertrophied gastric mucosa. With a rather broad differential diagnosis consisting of Zollinger-Ellison syndrome, hypertrophic lymphocytic gastritis, hypertrophic hypersecretory gastropathy, gastric adenocarcinoma, gastric polyps, infections such as histoplasmosis and tuberculosis, autoimmune-like inflammatory conditions such as sarcoidosis, and more commonly, gastrointestinal disease, it is often overlooked in the diagnostic workup. Therefore, it is crucial for clinicians to conduct a thorough evaluation and maintain a high clinical suspicion when there is concurrent H.pylori infection and/or imaging findings suggestive of hypertrophied gastric mucosa to avoid missing this disease.